Sistem Informasi Pengolahan Data Jaminan Instalasi Listrik Pelanggan (Jilp) Pada Asosiasi Kontraktor Ketenagalistrikan Indonesia (Aklindo) Pacitan - Julianto, Aditya; Purnama, Bambang Eka; Wardati, Indah Uly (Fakultas Teknologi Informatika Universitas Surakarta, 2014)
Abstract: Aklindo is a container berhimpunnya entities contracting with the electricity sector ( Chapter II, Article 4 ) , is independent and Nir profit . Aklindo have Dewan Pengurus Daerah ( DPD ) which took place in the provinces as well Dewan Pengurus Cabang ( DPC ) which is in the county or city . Also felt the need for computerization in activities related to archiving . This applies to a variety of institutions , companies and offices and also no exception Aklindo Pacitan . Which is one of the association that oversees several areas Ketengalistrikan CV is engaged in the electricity sector in Pacitan . One aspect that is vital to support the daily activities on Aklindo Pacitan is the data processing that goes on Aklindo JILP Pacitan . Therefore needed a system that could cope with it. Software used for the manufacture of this system is PHP . The purpose of this research is to create a data processing system JILP information on Aklindo Pacitan . The benefit is to facilitate the process of data recording JILP , customer data and cash data , preparing reports JILP of data , customer data , as well as cash data . The method used is literature , observation , interviews and analysis . Of making this system , hopes to ease the tasks of employees and data processing errors and anticipate JILP on Aklindo Pacitan . Keyword : Information Systems,